Arsitektur Cina pada Klenteng Jin De Yuan di Kawasan Pecinan Jakarta sebagai suatu Perwujudan Akulturasi Kebudayaan - Salim, Polniwati (Bina Nusantara University, 2012)
Cultural acculturation can be seen from various aspects, where the fusion of two cultural elements will not remove the could go to Indonesia and was applied to the temples in Indonesia, but still did not leave the cultural elements of Indonesia. Temple Jin De Yuan was one of the many temples in Jakarta, especially in the area of Chinatown, an area in terms of population, form of shelter, social order and the atmosphere of the environment had historically rooted characteristic of cultured Chinese people which was very thick with the architecture Chinese. Article presents how the application of Chinese architecture as a manifestation of Chinese culture and acculturation Indonesia in the temple Jin De Yuan can increase the cultural treasury of Indonesia. The research applied qualitative method and also library research.